Innovation, adaptation and foreign policy in the age of globalization: is Global Affairs Canada fit for purpose? - Copeland, Daryl (Canadian foreign policy journal, 2018)
The continuing evolution away from state-centricity requires that diplomacy become more public, inclusive and participatory. Responding to that imperative, and recognizing that the foreign ministry is not a cathedral, the foreign service is not a priesthood, and diplomacy is not liturgy, collectively represent the sine qua non for bringing Canada "back." By privileging talking over fighting, embracing innovation and re-thinking diplomatic practice and representation abroad, Canada can advance its interests, effectively pursue its policy goals and make a significant contribution to global peace and prosperity. Absent radical reform and a commitment to praxis, however, none of these outcomes is likely to eventuate. This commentary surveys the past 50 years of diplomatic history, assesses the current government's record to date, and suggests eight preconditions for real progress.